Optimalisasi Fintech Syariah Sebagai Agen Investasi Sukuk Negara - Trimulato, Trimulato (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
The development of the Islamic finance industry has provided a variety of Islamic financial products. Islamic finance is not only limited to products in Islamic banks. Currently, Islamic financial products have developed, including the presence of Sukuk Investment products. The existing Sukuk consist of state Sukuk and corporate Sukuk. In the marketing process, state Sukuk is still dominated by conventional financial institutions, even though Sukuk itself is a product of Islamic finance. one of the Islamic financial institutions as a Sukuk agent can go through sharia fintech. The purpose of the study was to determine the development of state Sukuk and the development of sharia fintech institutions. and to find out the optimization of sharia fintech as a state Sukuk investment agent. The research method used in this research is qualitative. The data source used is secondary data. The data has been presented by the Financial Services Authority (OJK) and the Directorate General of Financing and Risk Management (DJPPR) of the Ministry of Finance. The data analysis technique used in this study is descriptive qualitative, which describes the development of state Sukuk products, as well as the development of sharia fintech peer-to-peer lending (P2P) sharia, as well as forms of optimizing sharia fintech as a selling agent for state Sukuk products. The results of this study show that the development of state Sukuk of the SR type in 2019 reached 46.07 percent and ST type reached 8,436,570,000,000. As for the development of sharia fintech, sharia fintech assets amounted to 50,591,727,786 rupiahs or 1.4 percent of the total fintech assets as a whole. The number of fintech that has been registered and licensed at the OJK is 161 companies, and 7.5 percent are sharia fintech or 13 companies. Optimizing sharia fintech as a state Sukuk investment agent needs to be done, by involving sharia fintech as Sukuk. Reversing the essence of Sukuk as a sharia product can be obtained through sharia fintech, to be more convincing. The character of sharia fintech by utilizing technology can provide access to state Sukuk sharia investment.